Pengembangan LKPD Menulis Teks Eksposisi Berbasis Model Discovery Learning Siswa Kelas VIII - Fariz Hidayatulloh; Sumarti Sumarti; Farida Ariyani (Universitas Lampung, 2019)
This research relates to the development of the LKPD in writing an exposition text based on discovery learning model. It is aimed to produce a teaching material, to describe the properness of the teaching material, and to investigate the effectiveness of the teaching material which is the development of LKPD in writing an exposition text based on discovery learning model. The method of this research was adapted from 7 of 10 steps in the research procedure and development according to Borg and Gall. The result showed that 1) this research was successful to develop a teaching material which was LKPD in writing an exposition text based on discovery learning model, 2) the overall participant activities sheet was valid according to the material expert, media expert, and practitioner with the percentage values of 93, 80, 93.3, 3) the participant activities sheet was effective to improve the ability to write an exposition text in each school with the n-gain values of 0.48, 0.44, and 0.54 in which they were included in the medium category.Penelitian ini berkaitan dengan pengembangan LKPD menulis teks eksposisi berbasis model discovery learning. Tujuan penelitian yakni menghasilkan produk bahan ajar, mendeskripsikan kelayakan produk bahan ajar, dan menguji efektivitas bahan ajar berupa Pengembangan LKPD Menulis Teks Eksposisi Berbasis Model Discovery Learning. Metode penelitian menggunakan desain penelitian dan pengembangan yang mengadaptasi tujuh dari sepuluh langkah dalam prosedur penelitian dan pengembangan menurut Borg and Gall. Hasil penelitian menunjukkan bahwa 1) berhasil dikembangkan bahan ajar berupa LKPD Menulis Teks Eksposisi Berbasis Model Discovery Learning, 2) kelayakan lembar kegiatan peserta didik secara keseluruhan dinyatakan sangat layak oleh ahli materi, ahli media, dan praktisi dengan persentase penilaian 93, 80, dan 93, 3) lembar kegiatan peserta didik efektif meningkatkan kemampuan menulis teks ekposisi pada masing-masing sekolah dengan nilai N-gain sebesar (0,48), (0,44), dan (0,54) termasuk dalam kategori sedang.Kata kunci: model discovery learning, LKPD, teks ekpsosisi